Controlled and Tunable Biomimetic Apatite Mineralization of Synthetic Hydrogels. Issue 10 (October 2016) - Harding, Jacqueline L.; Krebs, Melissa D.
Abstract : The selective and predictable mineralization of polymeric hydrogels with CO3 2− and F − substituted apatites to mimic bone and dental mineralized matrix is demonstrated. The fabrication method provides the ability to tune calcium phosphate composite hydrogels for specific applications. Abstract : There has been much work examining bioinspired mineralization of polymeric hydrogels with calcium phosphates, yet a systematic method for the predictable and tunable synthesis of biomimetic apatites is yet to be developed. Here, a method for the selective mineralization of substituted apatite composite hydrogels where the incorporated mineral phase is formed as a result of a chemical reaction within the hydrogel matrix is presented. Mineralized hydrogels are prepared by precipitating the apatite precursor phase dicalcium phosphate dihydrate (DCPD) in a poly(vinyl alcohol) (PVA) solution, which is then crosslinked into a composite hydrogel by cyclic freeze/thawing. The encapsulated DCPD is hydrolyzed to apatite by immersion in buffers at 37 °C. Tuning the pH (7.4, 9) and ionic composition (CO3 2−, F − ) of the buffer influence the morphology and chemical composition of the apatite product. The incorporated calcium phosphate polymorph is monitored by X‐ray diffraction, attenuated total reflectance‐fourier transform infrared spectroscopy (ATR‐FTIR), and scanning electron microscope‐energy dispersive X‐ray. The apatite–PVA hydrogels promote cellular adhesion and viability. The method developed here demonstrates diffusion‐mediated transformation of a calcium phosphate precursor phase within a hydrogel matrix to various substituted apatites in a selective and predictable manner.